2015
DOI: 10.1007/s00330-015-3835-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of magnetic resonance elastography and diffusion-weighted imaging for differentiating benign and malignant liver lesions

Abstract: • MRE is superior to DWI for differentiating benign and malignant focal liver lesions. • Benign lesions with large fibrous components may have higher stiffness with MRE. • Cholangiocarcinomas tend to have higher stiffness than hepatocellular carcinomas. • Hepatocellular adenomas tend to have lower stiffness than focal nodular hyperplasia. • MRE is superior to conventional MRI in differentiating benign and malignant liver lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 28 publications
5
39
1
Order By: Relevance
“…A potential explanation for the difference in HCC stiffness may be due to different lesion inclusion. Stiffness values of 5.3 ± 2.2 kPa for cirrhotic background liver in our study are in line with the results of Venkatesh et al In another recent study by Hennedige et al [27] stiffness values of 55 untreated HCCs were evaluated. Using a similar MRE technique, the authors reported values of 7.7 ± 2.6 kPa, which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A potential explanation for the difference in HCC stiffness may be due to different lesion inclusion. Stiffness values of 5.3 ± 2.2 kPa for cirrhotic background liver in our study are in line with the results of Venkatesh et al In another recent study by Hennedige et al [27] stiffness values of 55 untreated HCCs were evaluated. Using a similar MRE technique, the authors reported values of 7.7 ± 2.6 kPa, which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Venkatesh et al [19] found a non-significant linear correlation between tumor size and stiffness and Hennedige et al [27] also reported an association between tumor size and stiffness. Our data show no such correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor stiffness (kPa) was measured by an independent observer blinded to the clinical and tumor pathologic data as previously described [23,24]. Regions of interest (ROI) were drawn on the elastograms covering the HCC and in the case of HCCs with non-enhancing/necrotic components, only the solid portion was included in the ROI.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic resonance elastography (MRE) is a noninvasive MRI based technique for quantitatively assessing the mechanical properties of tissues and has been used clinically most extensively in the liver as a quantitative tool for diagnosing and staging liver fibrosis [21,22]. Moreover, MRE has been shown to be feasible for measuring liver tumor stiffness (kPa) and is more accurate than diffusion-weighted imaging (DWI) for differentiating benign and malignant focal liver lesions [23,24]. However, it is not known if tumor stiffness by MRE can differentiate HCC tumor pathologic features.…”
Section: Introductionmentioning
confidence: 99%
“…Our conclusions are limited by the low number of NFHs taken into account (n=4). Regarding HCAs, a recent study sustained that their mean ADC value is significantly higher than that of malignant FLLs [28]. The result needs to be proved by further studies, but additional research is difficult due to the fact that HCAs are rare lesions and obtaining statistically relevant series will be difficult.…”
Section: Inter-observer Variabilitymentioning
confidence: 99%